HawkerSearch: an LLM-powered marketing platform for elderly and/or low tech literacy hawkers in Singapore - Oh, Malthus Teng Jie (Nanyang Technological University, 2024)
Hawker Culture in Singapore, recognised by UNESCO as an Intangible Cultural Heritage, is a vital part of our nation’s cultural and economic landscape. However, as technology continues to evolve and shape our society, an ageing and less tech-savvy hawker demographic remains disconnected from modern marketing techniques, widening the digital gap between hawkers and contemporary F&B establishments.